2019
DOI: 10.3390/su11071875
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Carbon Emission Driven by the Consumption of Carbohydrate-Rich Foods: The Case of China

Abstract: Background: Carbohydrate-rich (CR) foods are essential parts of the Chinese diet. However, CR foods are often given less attention than animal-based foods. The objectives of this study were to analyze the carbon emissions caused by CR foods and to generate sustainable diets with low climate impact and adequate nutrients. Methods: Twelve common CR food consumption records from 4857 individuals were analyzed using K-means clustering algorithms. Furthermore, linear programming was used to generate optimized diets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…Wynes & Nicholas (2018) reported that there were four human behaviors that can reduce carbon emissions: avoiding animal-based food consumption and shifting to plant-based (vegan) food consumption; reducing air transport; reducing motor vehicle usage; and having fewer children [16]. Individual behaviors that can reduce carbon emissions include reducing red meat consumption; shopping at traditional markets or local grocers; using bicycles for local transportation; shopping for fruit according to season to reduce waste due to damaged or rotten fruits; growing one's own groceries; and reducing the consumption of carbohydrate-rich foods [17]. Research has demonstrated that beef and lamb are the foods that produce the greatest carbon emissions per kg [18].…”
Section: Introductionmentioning
confidence: 99%
“…Wynes & Nicholas (2018) reported that there were four human behaviors that can reduce carbon emissions: avoiding animal-based food consumption and shifting to plant-based (vegan) food consumption; reducing air transport; reducing motor vehicle usage; and having fewer children [16]. Individual behaviors that can reduce carbon emissions include reducing red meat consumption; shopping at traditional markets or local grocers; using bicycles for local transportation; shopping for fruit according to season to reduce waste due to damaged or rotten fruits; growing one's own groceries; and reducing the consumption of carbohydrate-rich foods [17]. Research has demonstrated that beef and lamb are the foods that produce the greatest carbon emissions per kg [18].…”
Section: Introductionmentioning
confidence: 99%
“…For example, based on the input-output method, Feng et al (2020) found that, compared to 1992, China's per capita food consumption carbon emissions were reduced by 21% in 2007 [9]. Yang et al (2019) found that Chinese residents' food consumption carbon emissions were 683.38 g CO 2 -eq per day per capita based on the life cycle method, noting that optimizing dietary structure can reduce carbon emissions by 40% [24]. However, a comprehensive study on food consumption carbon emissions in China has not yet been completed [12], especially from a rural residents' perspective.…”
Section: Introductionmentioning
confidence: 99%